Blood Stain on the Throne - Obafemi, Yemi (Rasmed Publications Ltd, 2007)
As a child, Prince Adefemi had the natural aspiration of succeeding his aged father as the King Of Belewu. Unfortunately for him, the ways of the Gods is totally different from those of men.
Keywords: Juvenile Fiction